Analisis Peran Komisi Pemilihan Umum (KPU) dalam Partisipasi Politik Masyarakat di Pilkada serta Meminimalisir Golput - Siti dea nurindah Sari; Akhmad Shodikin; Sahrul Hanafi (Hukum, 2025)
Voter participation in regional head elections is central to democratic legitimacy, yet the 2024 simultaneous regional elections revealed substantial variation and participation below the national target. This study aims to formulate an institutional strategy for the General Elections Commission (Komisi Pemilihan Umum/KPU) to strengthen informed and inclusive voter participation while reducing involuntary and uninformed abstention. The research uses a qualitative integrative literature review. Legal documents, official KPU reports, books, and peer-reviewed articles were selected purposively from journal portals, Garuda, and official legal and electoral-document databases. The sources were analyzed thematically using the civic voluntarism model and the electoral management body perspective, focusing on resources, political engagement, mobilization, integrity, accessibility, and institutional coordination. The findings show that abstention is heterogeneous and cannot be treated solely as political apathy. Low turnout also results from administrative barriers, limited political efficacy, distrust, unequal information access, mobility constraints, and inaccessible polling services. KPU therefore needs an integrated strategy consisting of institutional integrity, segmented and continuous voter education, accessible electoral services, responsible digital communication, and multi-stakeholder collaboration supported by measurable evaluation. This study contributes the ILAK framework—integrity, literacy, accessibility, and collaboration—as a model for shifting KPU policy from event-based socialization toward a sustainable voter-participation ecosystem. The framework emphasizes that participation must be improved without coercing citizens or delegitimizing conscious political abstention.